2012
DOI: 10.1128/jvi.05937-11
|View full text |Cite
|
Sign up to set email alerts
|

Complex Dynamic Development of Poliovirus Membranous Replication Complexes

Abstract: Replication of all positive-strand RNA viruses is intimately associated with membranes. Here we utilize electron tomography and other methods to investigate the remodeling of membranes in poliovirus-infected cells. We found that the viral replication structures previously described as "vesicles" are in fact convoluted, branching chambers with complex and dynamic morphology. They are likely to originate from cis-Golgi membranes and are represented during the early stages of infection by singlewalled connecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
301
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 208 publications
(318 citation statements)
references
References 58 publications
14
301
3
Order By: Relevance
“…Similarly, other studies of membrane rearrangements during infection with Kunjin and West Nile virus suggest that Golgi proteins are indeed recruited to replication sites (36,47,48). Moreover, based on electron microscopy studies, it was suggested that Golgi membranes are the initial sites of poliovirus replication complexes (35). In this context our results highlight a previously unexplored role for IRGM as a Golgi protein that contributes to HCV replication.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Similarly, other studies of membrane rearrangements during infection with Kunjin and West Nile virus suggest that Golgi proteins are indeed recruited to replication sites (36,47,48). Moreover, based on electron microscopy studies, it was suggested that Golgi membranes are the initial sites of poliovirus replication complexes (35). In this context our results highlight a previously unexplored role for IRGM as a Golgi protein that contributes to HCV replication.…”
Section: Discussionsupporting
confidence: 62%
“…GBF1 and Arf1, proteins that conserve Golgi maintenance and function, are known to be crucial for the replication of certain RNA viruses, such as enteroviruses (17), possibly by recruitment of PI4KIIIβ to viral replication sites. Indeed, recent data have revealed that the Golgi membrane and Golgi proteins may have a previously unappreciated role in the replication of Enterovirus and Flavivirus (35,36). Moreover, GBF1 and Arf1 have been suggested to be host factors for HCV (18)(19)(20).…”
Section: Resultsmentioning
confidence: 99%
“…7, inset 1b). Vesicles shaped in this way have been described as appearing in chronological order in rosette-like structures observed during poliovirus infection (Belov et al, 2012). It is also unknown whether the proportion of double-membraned vesicles increases with infection and the role, if any, that they play.…”
Section: Discussionmentioning
confidence: 99%
“…These three viruses infect plants or humans and belong to the alphavirus-, flavivirius-, or picornavirus-like superfamily, respectively. They also induce very different membrane-bound VRCs: BMV forms single-membrane spherules that remain connected to the ER membrane (6), whereas HCV forms convoluted membrane webs and DMVs (double-membrane vesicles) (37) and poliovirus induces DMVs and tubular structures (38). Despite the topological differences in VRC structures, these viruses specifically promoted PC synthesis/ accumulation at the viral replication sites, suggesting a common feature shared by them and possibly by other (+)RNA viruses.…”
Section: Discussionmentioning
confidence: 99%